Transformation Financial Services Authority in the Digitalization Era - Master Irfan Ibrahim; Dabella Yunia (PT. EQUATOR SINAR AKADEMIA, 2022)
Research aim for analyze policies and regulations and Steps _ develop Financial Services Industry , strengthening institutional Financial Services Authority , the role of OJK as part from Committee Stability System Finance . Method research used in research _ is method descriptive . Researcher analyze based on source reference as Regulation Government , Laws and Regulations from Financial Services Authority . Research results consist on Policies and regulations and Steps _ develop Financial Services Industry has regulated by law Number 21 of 2011 which can be applied with a number of stage , that is Step preparation , implementation and evaluation . Strengthening institutional Financial Services Authority performed on various aspect , that is aspect services , resources people and budget institution . OJK's role as part from Committee Stability System Finance done with guard stability system finance could done with response and synergy policy .